Design method of high thermal conductivity multi-component magnesium alloy solid solution and magnesium alloy solid solution
Patent Information
- Application Number
- CN202410664338.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-27
AI Technical Summary
但这种方法容易导致基体强度低,最终合金整体强度弱
[0035]1、本发明采用向含有单一固溶元素的二元镁基体中添加特定筛选的满足一定原子尺寸、电负性、比例的其它固溶元素,形成多组元固溶交互作用,既能保证固溶体维持高热导率,又能解决固溶体导热和强度的矛盾问题,实现高导热和高强度的兼得;两种固溶元素存在于基体中,还有助于维持基体的固溶强化效果,保证基体强度。
Smart Images

Figure CN118447980B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a material design method, and more specifically to a design method for high thermal conductivity magnesium alloy solid solutions and magnesium alloy solid solutions. Background Technology
[0002] Magnesium alloys are widely used in the automotive and 3C electronics industries. With the rapid development of these industries, components are required to possess excellent mechanical properties while also ensuring good heat dissipation, thus placing higher demands on their thermal conductivity. Alloying is the primary method to improve the strength of magnesium alloys. After alloying, the microstructure of the alloy mainly consists of a matrix (solid solution) and a second phase. Some alloying elements exist in the matrix as solid solution atoms, while the remaining alloying elements exist as the second phase. As described in existing technologies (Metallurgical and Materials Transactions A, 2022, 53:2730–2742; Metallurgical and Materials Transactions A, 2019, 50:5969–5976; and Metallurgical and Materials Transactions A, 2016, 50:4104–4115), the matrix generally accounts for more than 80% of the entire microstructure; therefore, the strength of the alloy is mainly determined by the matrix. However, strength and thermal conductivity are often contradictory; after alloying, both solid solution atoms and the second phase worsen the thermal conductivity of the magnesium alloy. However, compared to the second phase, solid solution atoms are the core factor affecting the thermal conductivity of the alloy. According to the reference (Journal of Alloys and Compounds, 2018, 747: 431-437), for solid solutions and second phases containing equal amounts of alloying elements, the effect of solid solution atoms on the thermal conductivity of the alloy is ten times that of the second phase.
[0003] The main reason is that, compared to pure metals, alloying elements are impurities that cause lattice distortion in magnesium, becoming scattering sources for electron and phonon transport, reducing the mean free path of electrons and phonons, and thus lowering the thermal conductivity. However, the lattice distortion caused by solid-solution atoms is much greater than that caused by the second phase. Solid-solution atoms disrupt the periodic arrangement of the lattice throughout the magnesium matrix, while the second phase only disrupts the periodicity at the interface between the second phase and the matrix (Materials Science and Engineering A, 2022, 861:144336). Therefore, it is generally believed in the industry that increasing the content of solid-solution atoms will inevitably lead to a decrease in thermal conductivity. The main approach to developing high thermal conductivity magnesium alloys is to avoid the presence of solid-solution atoms in the matrix and to precipitate them out as much as possible, transforming them into the second phase to reduce the concentration of solid-solution atoms in the matrix. However, this method easily leads to low matrix strength, resulting in a weak overall alloy strength. Therefore, the direction this invention aims to address is to ensure both the strength of the alloy matrix and excellent thermal conductivity.
[0004] Against this backdrop, this invention proposes a design method to improve thermal conductivity by increasing the content of solid solution atoms. This method involves adding an appropriate amount of a second solid solution element to a solid solution containing a single solid solution element. The two types of solid solution atoms must satisfy the following conditions: the electronegativity difference between them is greater than the electronegativity difference between them individually and Mg atoms; their atomic radii cannot both be greater than or less than the atomic radius of Mg; and the solidification rate during the solid solution preparation process must be greater than 400 K / s. This design method provides broader scope and greater possibilities for enriching the system of high thermal conductivity magnesium alloys and improving their performance. Summary of the Invention
[0005] In view of this, the present invention provides a design method for high thermal conductivity multi-component magnesium alloy solid solutions and a magnesium alloy solid solution thereof. This design method provides a broader scope and greater possibilities for enriching the system of high thermal conductivity magnesium alloys and improving their performance.
[0006] The technical solution provided by this invention is as follows:
[0007] <First Aspect>
[0008] A method for designing a high thermal conductivity multi-component magnesium alloy solid solution, the method comprising the following steps:
[0009] S1. Magnesium was chosen as the matrix element;
[0010] S2. Choose metal element A, which has a certain solid solubility in the magnesium matrix; choose metal element B, which also has a certain solid solubility in the magnesium matrix.
[0011] S3. Confirm the content of selected metal element A and metal element B: The ratio of the atomic percentage at.% of element B in the magnesium matrix to the atomic percentage at.% of element A in the magnesium matrix is denoted as E; if E≤4, the content of metal element A and metal element B is qualified; if E>4, the content of metal element A and metal element B is unqualified and the content needs to be re-determined.
[0012] Determine the electronegativity of metal element A and metal element B; denot the absolute value of the electronegativity difference between metal element A and Mg atom as Y1, the absolute value of the electronegativity difference between metal element B and Mg atom as Y2, and the absolute value of the electronegativity difference between metal element B and metal element A as Y3; if Y3 is greater than both Y1 and Y2, metal element A and metal element B are qualified; otherwise, metal element A and metal element B are unqualified.
[0013] Determine the atomic radii of metal element A and metal element B; determine whether the atomic radii of metal element A and metal element B are both greater than or both less than the atomic radius of Mg; if not, then metal element A and metal element B are qualified; if so, then metal element A and metal element B are unqualified.
[0014] In S1, the solid solubility limit of element A in the magnesium matrix is ≥1 at.%; the solid solubility limit of element B in the magnesium matrix is ≥1 at.%.
[0015] <Second aspect>
[0016] The present invention also provides a method for preparing a magnesium alloy solid solution, characterized by comprising the following steps:
[0017] 1) Using the design method for high thermal conductivity multi-component magnesium alloy solid solution as described in claim 1 or 2, confirm metal element A and its content; and metal element B and its content;
[0018] 2) Weigh the raw materials according to the stoichiometric ratio; add element A to the magnesium matrix, melt, and obtain Mg-A alloy melt;
[0019] 3) Add element B to the Mg-A alloy melt, melt it, and obtain the Mg-AB alloy melt;
[0020] 4) Solidify the Mg-AB alloy melt at a certain solidification rate and cool it to ambient temperature to obtain the magnesium alloy solid solution.
[0021] In step 2), the melting conditions are: temperature 700-800℃, time 60-100min.
[0022] In step 2), melting is carried out under a protective atmosphere, which includes SF6 and CO2.
[0023] In step 3), the melting conditions are: temperature 700-800℃, time 10-30min.
[0024] In step 4), the solidification rate is 400-800 K / s. In steps 6 and 7 of this invention, controlling the alloy to solidify at a solidification rate of 400-800 K / s is to ensure that the alloying elements exist as much as possible in the form of solute atoms, and to avoid the alloying elements precipitating out completely in the form of the second phase.
[0025] Element A is selected from Gd or Al; element B is selected from Al, Zn, or Gd; elements A and B are not the same.
[0026] The magnesium alloy solid solution prepared by the aforementioned method is also within the scope of protection of this invention.
[0027] The magnesium alloy solid solution includes Mg-4Gd-2Al solid solution or Mg-2Gd-1Zn solid solution.
[0028] As one embodiment of the present invention, the present invention provides a design method for a high thermal conductivity multi-component magnesium alloy solid solution, comprising the following steps:
[0029] Step 1: Select magnesium as the matrix element;
[0030] Step 2: Select metal element A and determine its content. The solid solubility limit of metal element A in the magnesium matrix is ≥1 at.%. Select metal element B and determine its content. The solid solubility limit of metal element B in the magnesium matrix is ≥1 at.%.
[0031] Step 3: The ratio of the atomic percentage (at.%) of metal element B in the magnesium matrix to the atomic percentage (at.%) of metal element A in the magnesium matrix is denoted as E. If E≤4, the content of metal element A and metal element B is qualified; if E>4, the content of metal element A and metal element B is unqualified and the content needs to be re-determined (E>4 will cause an excess of element B. Excessive B will not have A to agglomerate with, which will form additional lattice distortion and the thermal conductivity will decrease).
[0032] Determine the electronegativity of metal element A and metal element B; the absolute value of the electronegativity difference between metal element A and Mg atoms is denoted as Y1, the absolute value of the electronegativity difference between metal element B and Mg atoms is denoted as Y2, and the absolute value of the electronegativity difference between metal element B and metal element A is denoted as Y3; Y3 is greater than Y1 and Y2; if this condition is met, metal elements A and B are qualified; if not, metal elements A and B are unqualified, and the metal element is unqualified (the absolute value of the electronegativity difference between metal element B and metal element A must be greater than the absolute value of their respective electronegativity differences with Mg atoms in order to cause metal element B to agglomerate with metal element A).
[0033] Determine the atomic radii of metal elements A and B; determine if both atomic radii of metal elements A and B are greater than or less than the radius of a Mg atom; if not, then metal elements A and B are qualified; if so, then metal elements A and B are unqualified. The atomic radii of elements B and A must not both be greater than or less than the radius of a Mg atom to reduce lattice distortion when the two elements segregate.
[0034] The beneficial effects of this invention are as follows:
[0035] 1. This invention involves adding other solid solution elements that meet specific screening criteria, atomic size, electronegativity, and proportion to a binary magnesium matrix containing a single solid solution element. This forms a multi-component solid solution interaction, which can ensure that the solid solution maintains high thermal conductivity and solve the contradiction between thermal conductivity and strength, thus achieving both high thermal conductivity and high strength. The presence of two solid solution elements in the matrix also helps to maintain the solid solution strengthening effect of the matrix and ensure the strength of the matrix.
[0036] 2. The aggregation of two solid solution elements reduces the lattice distortion caused by a single solid solution element, thereby increasing the mean free path of electrons and phonons and contributing to the improvement of the thermal conductivity of the solid solution. Therefore, this invention found that the ratio of the atomic percentage (at.%) of element B in the magnesium matrix to the atomic percentage (at.%) of element A in the magnesium matrix is denoted as E, and E needs to be ≤4. If E > 4, it will cause an excess of element B. Excess B will not have A to aggregate with, resulting in additional lattice distortion and a decrease in thermal conductivity. In order for B and A to aggregate, the absolute value of the electronegativity difference between element B and element A needs to be greater than the absolute value of the electronegativity difference between them and Mg atoms respectively. In order to reduce lattice distortion when the two elements aggregate, the atomic radii of elements B and A must not both be greater than or less than the radius of Mg atoms.
[0037] 3. This invention provides valuable design ideas for the development of high thermal conductivity magnesium alloys, and opens up a wider space and greater possibilities for enriching the system and improving the performance of high thermal conductivity magnesium alloys.
[0038] 4. This method involves adding a second solid solution element to the magnesium alloy solid solution (based on the first solid solution element). The electronegativity difference between the single solid solution element and the second solid solution element must be greater than the electronegativity difference between them and Mg atoms. The atomic radii of the single solid solution element and the second solid solution element must not both be greater than or less than the radius of Mg atoms. The solidification rate during the solid solution preparation process must be greater than 400 K / s. Attached Figure Description
[0039] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:
[0040] Figure 1This diagram shows the microstructure of the Mg-4Gd solid solution in Embodiment 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 of the present invention.
[0041] Figure 2 This diagram shows the microstructure of the Mg-4Gd-2Al solid solution in Example 1 of the present invention.
[0042] Figure 3 The diagram shows the microstructure of the Mg-3Gd solid solution in Embodiment 2, Comparative Example 5, and Comparative Example 6 of the present invention.
[0043] Figure 4 This diagram shows the microstructure of the Mg-3Gd-1Al solid solution in Example 2 of the present invention.
[0044] Figure 5 This diagram shows the microstructure of the Mg-2Gd solid solution in Example 3 of the present invention.
[0045] Figure 6 This diagram shows the microstructure of the Mg-2Gd-1Zn solid solution in Example 3 of the present invention.
[0046] Figure 7 This diagram shows the microstructure of the Mg-4Gd-8Al solid solution in Comparative Example 1 of the present invention.
[0047] Figure 8 This diagram shows the microstructure of the Mg-2Al solid solution in Comparative Example 2 of the present invention.
[0048] Figure 9 This diagram shows the microstructure of the Mg-2Al-1Zn solid solution in Comparative Example 2 of the present invention.
[0049] Figure 10 A schematic diagram of the microstructure of the Mg-4Gd-0.5Li solid solution in Comparative Example 3 of the present invention is shown.
[0050] Figure 11 This diagram shows the microstructure of the Mg-4Gd-1Y solid solution in Comparative Example 4 of the present invention.
[0051] Figure 12 This diagram shows the microstructure of the Mg-3Gd-4Al solid solution in Comparative Example 5 of the present invention.
[0052] Figure 13 A schematic diagram of the microstructure of the Mg-3Gd-5Zn solid solution in Comparative Example 6 of the present invention is shown. Detailed Implementation
[0053] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.
[0054] This invention provides a design method for high thermal conductivity multi-component magnesium alloy solid solutions and their application.
[0055] The design method for the high thermal conductivity multi-component magnesium alloy solid solution includes the following steps:
[0056] Step 1: Select magnesium as the matrix element;
[0057] Step 2: Select metal element A and metal element B:
[0058] Element A has a solid solubility limit of ≥1 at.% in the magnesium matrix (if the solid solubility limit of element A is ≥1 at.%, then element A is qualified; if the solid solubility limit of element A is <1 at.%, then the element is unqualified, and metal element A should be selected again).
[0059] The solid solubility limit of element B in the magnesium matrix is ≥1 at.% (if the solid solubility limit of element B is ≥1 at.%, then element B is qualified; if the solid solubility limit of element B is <1 at.%, then the element is unqualified and the alloying element should be reselected).
[0060] Step 3:
[0061] Confirm the content of metal element A and metal element B:
[0062] The ratio of the atomic percentage (at.%) of element B in the magnesium matrix to the atomic percentage (at.%) of element A in the magnesium matrix is denoted as E. E≤4 (if E≤4, the content of metal element A and metal element B is qualified; if E>4, the content of metal element A and metal element B is unqualified and the content needs to be re-determined).
[0063] Determine the electronegativity of metal element A and metal element B:
[0064] The absolute value of the electronegativity difference between metal element A and Mg atom is denoted as Y1, the absolute value of the electronegativity difference between metal element B and Mg atom is denoted as Y2, and the absolute value of the electronegativity difference between metal element B and metal element A is denoted as Y3. Y3 must be greater than Y1 and Y2. If this condition is met, proceed to the next step. If not, the metal element is not qualified.
[0065] Determine the atomic radii of metal element A and metal element B:
[0066] Determine whether the atomic radii of metal element A and metal element B are both greater than or both less than the radius of Mg atom; if not, then metal element A and metal element B are qualified; if so, then metal element A and metal element B are unqualified.
[0067] Example 1
[0068] (I) Metal element A and metal element B and their amounts
[0069] Step 1: Select Mg as the matrix element.
[0070] Step 2: Select metal element A and metal element B:
[0071] The first element, Gd, was chosen because its solid solubility in magnesium is 4.53 at.%, which is greater than 1 at.%.
[0072] The second element, Al, was chosen because its solid solubility in magnesium is 11.44 at.%, which is greater than 1 at.%.
[0073] Step 3:
[0074] Confirm the content of metal element A and metal element B:
[0075] Gd, 4 wt.% (in the magnesium matrix);
[0076] Al, 2 wt.% (in the magnesium matrix);
[0077] Based on the conversion formula between mass fraction and atomic percentage:
[0078] Mass percentage of Gd = atomic percentage of Gd × atomic weight of Gd / (atomic percentage of Gd × atomic weight of Gd + atomic percentage of Al × atomic weight of Al + atomic percentage of Mg × atomic weight of Mg);
[0079] Mass percentage of Al = atomic percentage of Al × atomic weight of Al / (atomic percentage of Gd × atomic weight of Gd + atomic percentage of Al × atomic weight of Al + atomic percentage of Mg × atomic weight of Mg);
[0080] The atomic percentages of Al in the magnesium matrix were calculated to be 1.87 at.% and Gd to be 0.64 at.%; E = 2.92 for both, which is less than 4.
[0081] Determine the electronegativity of metal element A and metal element B:
[0082] The electronegativity of Gd is 1.2, that of Al is 1.61, and that of Mg is 1.31. The absolute value of the difference between the electronegativity of Gd and Mg is 0.11; the absolute value of the difference between the electronegativity of Al and Mg is 0.30; and the absolute value of the difference between the electronegativity of Gd and Al is 0.41.
[0083] The absolute value of the electronegativity difference between Gd and Al is greater than the absolute values of the electronegativity differences between Gd and Al and Mg, respectively.
[0084] Determine the atomic radii of metal element A and metal element B:
[0085] The atomic radius of Gd is The atomic radius of Al is The atomic radius of Mg is Atomic radius order: Gd > Mg > Al;
[0086] Gd and Al meet the requirements.
[0087] (II) Preparation of Mg-4Gd solid solution
[0088] 1) Based on the alloy composition and stoichiometric ratio, and considering the loss of Gd during the smelting process, the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, were deoxideized and placed in an oven for preheating at 200℃. The crucibles, coated with release agent, were then placed in the oven for drying.
[0089] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and pour into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-4Gd solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 78 W / (m·K).
[0090] (III) Mg-4Gd-2Al solid solution
[0091] 1) Based on the alloy composition and stoichiometric ratio, and considering the loss of Gd and Al during the smelting process, the required raw materials, including industrial pure magnesium ingots, Mg-Gd master alloy, and pure Al, were deoxideized and placed in an oven for preheating at 200℃. The crucibles, coated with release agent, were then placed in the oven for drying.
[0092] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add a Mg-Gd master alloy. Obtain a molten Mg-Gd alloy melt. Once the temperature drops to 700℃, add pure Al to the Mg-Gd alloy melt. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and heat to 750℃. Cast the molten Mg-Gd-Al alloy into a mold, controlling the solidification rate at 500 K / s, and cool to room temperature. Obtain a Mg-4Gd-2Al solid solution. Measure its thermal conductivity using ASTM-E1461, which is 101 W / (m·K).
[0093] Figure 1 and Figure 2 The microstructures of Mg-4Gd solid solution and Mg-4Gd-2Al solid solution are shown respectively. The comparison shows that the addition of 2wt.%Al to Mg-4Gd solid solution causes Al and Gd segregation, reduces the lattice distortion caused by Gd atoms, makes electrons less likely to be scattered during transport, increases the path of freedom, and thus increases the thermal conductivity by 29.5%.
[0094] The thermal conductivity of Mg-4Gd-2Al solid solution is greater than that of Mg-4Gd solid solution, indicating that adding appropriate amounts of multi-component solid solution elements can improve the thermal conductivity of Mg solid solution.
[0095] Example 2
[0096] (I) Metal element A and metal element B and their amounts
[0097] Step 1: Select Mg as the matrix element.
[0098] Step 2: Select metal element A and metal element B:
[0099] The first element, Gd, was chosen because its solid solubility in magnesium is 4.53 at.%, which is greater than 1 at.%.
[0100] The second element, Al, was chosen because its solid solubility in magnesium is 11.44 at.%, which is greater than 1 at.%.
[0101] Step 3:
[0102] Confirm the content of metal element A and metal element B:
[0103] Gd, 3 wt.% (in the magnesium matrix);
[0104] Al, 1 wt.% (in the magnesium matrix);
[0105] Based on the conversion formula between mass fraction and atomic percentage:
[0106] Mass percentage of Gd = atomic percentage of Gd × atomic weight of Gd / (atomic percentage of Gd × atomic weight of Gd + atomic percentage of Al × atomic weight of Al + atomic percentage of Mg × atomic weight of Mg);
[0107] Mass percentage of Al = Atomic percentage of Al × Atomic weight of Al / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Al × Atomic weight of Al + Atomic percentage of Mg × Atomic weight of Mg).
[0108] The atomic percentages of Al in the magnesium matrix were calculated to be 0.93 at.% and Gd in the magnesium matrix to be 0.48 at.%; E = 1.94 for both, which is less than 4.
[0109] Determine the electronegativity of metal element A and metal element B: Same as in Example 1;
[0110] Determine the atomic radii of metal element A and metal element B: Same as in Example 1.
[0111] (II) Preparation of Mg-3Gd solid solution
[0112] 1) Based on the alloy composition and stoichiometric ratio, and considering the loss of Gd during the smelting process, the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, were deoxideized and placed in an oven for preheating at 200℃. The crucibles, coated with release agent, were then placed in the oven for drying.
[0113] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and pour into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-4Gd solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 78 W / (m·K).
[0114] (III) Mg-3Gd-1Al solid solution
[0115] 1) Based on the alloy composition and stoichiometric ratio, and considering the loss of Gd and Al during the smelting process, the required raw materials, including industrial pure magnesium ingots, Mg-Gd master alloy, and pure Al, were deoxideized and placed in an oven for preheating at 200℃. The crucibles, coated with release agent, were then placed in the oven for drying.
[0116] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add a Mg-Gd master alloy. Obtain a molten Mg-Gd alloy melt. Once the temperature drops to 700℃, add pure Al to the Mg-Gd alloy melt. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and heat to 750℃. Cast the molten Mg-Gd-Al alloy into a mold, controlling the solidification rate at 500 K / s, and cool to room temperature. Obtain a Mg-4Gd-1Al solid solution. Measure its thermal conductivity using ASTM-E1461 standard; it is 85 W / (m·K).
[0117] Figure 3 and Figure 4 The microstructures of Mg-3Gd solid solution and Mg-3Gd-1Al solid solution are shown respectively. The comparison shows that the addition of 1 wt.% Al to Mg-3Gd solid solution causes Al and Gd segregation, reduces the lattice distortion caused by Gd atoms, and makes some electrons less likely to be scattered during transport, thus increasing the path of freedom and improving the thermal conductivity by 29.4%.
[0118] The thermal conductivity of Mg-3Gd-1Al solid solution is greater than that of Mg-3Gd solid solution, indicating that adding appropriate amounts of multi-component solid solution elements can improve the thermal conductivity of Mg solid solution.
[0119] Example 3
[0120] (I) Metal element A and metal element B and their amounts
[0121] Step 1: Select Mg as the matrix element.
[0122] Step 2: Select metal element A and metal element B.
[0123] The first alloying element selected is Gd, whose solid solubility in magnesium is 4.53 at.%, which is greater than 1 at.%.
[0124] The second alloying element, Zn, was chosen. Zn has a solid solubility of 2.4 at.% in magnesium, which is greater than 1 at.%.
[0125] Step 3: Confirm the content of metal element A and metal element B:
[0126] Gd, taken as 2 wt.% (content in the magnesium matrix);
[0127] Zn, taken as 1 wt.% (content in the magnesium matrix);
[0128] Based on the conversion formula between mass fraction and atomic percentage: Mass percentage of Gd = Atomic percentage of Gd × Atomic weight of Gd / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Zn × Atomic weight of Zn + Atomic percentage of Mg × Atomic weight of Mg); Mass percentage of Zn = Atomic percentage of Zn × Atomic weight of Zn / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Zn × Atomic weight of Zn + Atomic percentage of Mg × Atomic weight of Mg). Solving for Zn in the magnesium matrix yields an atomic percentage of 0.38 at.% and Gd in the magnesium matrix, respectively; E = 1.19, which is less than 4.
[0129] Determine the electronegativity of metal element A and metal element B:
[0130] The electronegativity of Gd is 1.2, that of Zn is 1.65, and that of Mg is 1.31. The absolute value of the difference between the electronegativity of Gd and Mg is 0.11; the absolute value of the difference between the electronegativity of Zn and Mg is 0.34; and the absolute value of the difference between the electronegativity of Gd and Zn is 0.45.
[0131] The absolute value of the electronegativity difference between Gd and Zn is greater than the absolute value of the electronegativity difference between Gd and Zn and Mg, respectively.
[0132] Determine the atomic radii of metal element A and metal element B:
[0133] The atomic radius of Gd is The atomic radius of Zn is The atomic radius of Mg is Atomic radius order: Gd > Mg > Zn;
[0134] Gd and Zn meet the requirements.
[0135] (II) Preparation of Mg-2Gd solid solution
[0136] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, and preheat them in an oven at 200℃. Place the crucibles coated with release agent into the oven to dry.
[0137] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and pour the molten Mg-Gd alloy into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-2Gd solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 93 W / (m·K).
[0138] (III) Mg-2Gd-1Zn solid solution
[0139] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd and Zn during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots, Mg-Gd master alloy, and pure Zn, and preheat them in an oven at 200℃. Place the crucibles, coated with release agent, into the oven to dry.
[0140] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. After obtaining the molten Mg-Gd metal, lower the temperature to 700℃ and add Zn (pure Zn) to the Mg-Gd alloy melt. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, heat to 750℃, and pour the molten Mg-Gd-Zn alloy into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-2Gd-1Zn solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 118 W / (m·K).
[0141] Figure 5 and Figure 6 The microstructures of Mg-2Gd solid solution and Mg-2Gd-1Zn solid solution are shown respectively. The comparison shows that the addition of 1 wt.% Zn to Mg-2Gd solid solution causes Zn and Gd segregation, reduces the lattice distortion caused by Gd atoms, makes electrons less susceptible to scattering during transport, increases the path of freedom, and thus increases the thermal conductivity by 26.9%.
[0142] The thermal conductivity of Mg-2Gd-1Zn solid solution is greater than that of Mg-2Gd solid solution, indicating that adding appropriate amounts of multi-component solid solution elements can improve the thermal conductivity of Mg solid solution.
[0143] Comparative Example 1
[0144] (I) Metal element A and metal element B and their amounts
[0145] Step 1: Select Mg as the matrix element.
[0146] Step 2: Select metal element A and metal element B:
[0147] The first element, Gd, was chosen because its solid solubility in magnesium is 4.53 at.%, which is greater than 1 at.%.
[0148] The second element, Al, was chosen because its solid solubility in magnesium is 11.44 at.%, which is greater than 1 at.%.
[0149] Step 3: Confirm the content of metal element A and metal element B:
[0150] Gd, taken as 4 wt.% (content in the magnesium matrix);
[0151] Al, taken as 8 wt.% (content in the magnesium matrix);
[0152] Based on the conversion formula between mass fraction and atomic percentage: Mass percentage of Gd = Atomic percentage of Gd × Atomic weight of Gd / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Al × Atomic weight of Al + Atomic percentage of Mg × Atomic weight of Mg); Mass percentage of Al = Atomic percentage of Al × Atomic weight of Al / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Al × Atomic weight of Al + Atomic percentage of Mg × Atomic weight of Mg). Solving for the atomic percentage of Al in the magnesium matrix, we find it to be 7.52 at.%, and the atomic percentage of Gd in the magnesium matrix to be 0.64 at.%. The E = 11.75, which is greater than 4.
[0153] Determine the electronegativity of metal element A and metal element B: Same as in Example 1;
[0154] Determine the atomic radii of metal element A and metal element B: Same as in Example 1.
[0155] (II) Preparation of Mg-4Gd solid solution
[0156] 1) Based on the alloy composition and stoichiometric ratio, and considering the loss of Gd during the smelting process, the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, were deoxideized and placed in an oven for preheating at 200℃. The crucibles, coated with release agent, were then placed in the oven for drying.
[0157] 2) Place the industrial pure magnesium ingot into a crucible, heat up to 760°C under a protective atmosphere of a mixed gas of SF6 and CO2 (volume ratio 60:1). After 80 minutes, when the pure magnesium is melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, hold for 20 minutes, skim off the slag, pour into a mold, control the alloy to solidify at a solidification rate of 500K / s, and cool to room temperature. A Mg-4Gd solid solution is obtained, and its thermal conductivity is measured to be 78W / (m·K) using the ASTM-E1461 test standard.
[0158] (3) Preparation of Mg-4Gd-8Al solid solution
[0159] 1) According to the alloy composition and stoichiometric ratio, considering the burning loss of Gd and Al during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingot, Mg-Gd master alloy and pure Al, and preheat them in an oven at 200°C. Put the crucible coated with a release agent into the oven together for drying;
[0160] 2) Place the industrial pure magnesium ingot into a crucible, heat up to 760°C under a protective atmosphere of a mixed gas of SF6 and CO2 (volume ratio 60:1). After 80 minutes, when the pure magnesium is melted, add the Mg-Gd master alloy. After obtaining the molten Mg-Gd metal liquid, when the temperature drops to 700°C, add Al in the form of pure Al into the Mg-Gd alloy melt, stir thoroughly for 15 minutes, hold for 20 minutes, skim off the slag, heat up to 750°C, transfer the molten Mg-Gd-Al alloy into a mold, control the alloy to solidify at a solidification rate of 500K / s, and cool to room temperature. A Mg-4Gd-8Al solid solution is obtained, and its thermal conductivity is measured to be 45W / (m·K) using the ASTM-E1461 test standard.
[0161] Figure 7 shows the schematic microstructure of the Mg-4Gd-8Al solid solution, and by comparison Figure 1 it can be seen that adding 8wt.% Al to the Mg-4Gd solid solution results in not only segregation of part of Al and Gd, but also excess Al uniformly dispersed in the magnesium matrix. Although the segregation of Al and Gd reduces the lattice distortion caused by Gd atoms, the excess Al atoms will cause additional lattice distortion, leading to scattering of electrons during transport, the free path is instead reduced, thereby the thermal conductivity decreases.
[0162] The thermal conductivity of Mg-4Gd-8Al solid solution < the thermal conductivity of Mg-4Gd solid solution, which indicates that adding excessive multi-component solid solution elements will reduce the thermal conductivity of the Mg-4Gd solid solution.
[0163] Comparative Example 2
[0164] (1) Metal element A, metal element B and their dosages
[0165] Step 1: Select Mg as the matrix element.
[0166] Step 2: Select metal element A and metal element B:
[0167] The first metallic element chosen is Al, whose solid solubility in magnesium is 11.44 at.%, which is greater than 1 at.%.
[0168] The second alloying element, Zn, was chosen. Zn has a solid solubility of 2.4 at.% in magnesium, which is greater than 1 at.%.
[0169] Step 3: Confirm the content of metal element A and metal element B:
[0170] Al, taken as 2 wt.% (content in the magnesium matrix);
[0171] Zn, taken as 1 wt.% (content in the magnesium matrix);
[0172] Based on the conversion formula between mass fraction and atomic percentage: Mass percentage of Zn = Atomic percentage of Zn × Atomic weight of Zn / (Atomic percentage of Zn × Atomic weight of Zn + Atomic percentage of Al × Atomic weight of Al + Atomic percentage of Mg × Atomic weight of Mg); Mass percentage of Al = Atomic percentage of Al × Atomic weight of Al / (Atomic percentage of Zn × Atomic weight of Zn + Atomic percentage of Al × Atomic weight of Al + Atomic percentage of Mg × Atomic weight of Mg). Solving for Zn in the magnesium matrix yields 0.37 at.%; Atomic percentage of Al in the magnesium matrix is 1.82 at.%, and E = 0.2, which is less than 4.
[0173] Determine the electronegativity of metal element A and metal element B:
[0174] The electronegativity of Al is 1.61, that of Zn is 1.65, and that of Mg is 1.31. The absolute value of the difference between the electronegativity of Al and Mg is 0.30; the absolute value of the difference between the electronegativity of Zn and Mg is 0.34; and the absolute value of the difference between the electronegativity of Al and Zn is 0.04.
[0175] The absolute value of the electronegativity difference between Al and Zn is less than the absolute value of the electronegativity difference between Al and Zn and Mg, respectively.
[0176] Determine the atomic radii of metal element A and metal element B:
[0177] The atomic radius of Al is The atomic radius of Zn is The atomic radius of Mg is Atomic radius order: Mg > Al > Zn.
[0178] (II) Preparation of Mg-2Al solid solution
[0179] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Al during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots and pure Al, and preheat them in an oven at 200℃. Place the crucibles, coated with release agent, into the oven to dry.
[0180] 2) Place industrial pure magnesium ingots in a crucible and heat to 720℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add Al as pure Al to the melt. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, maintain the temperature at 720℃, and pour the molten Mg-Al alloy into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain Mg-2Al solid solution. Measure its thermal conductivity using ASTM-E1461 standard; it is 98 W / (m·K).
[0181] (III) Mg-2Al-1Zn solid solution
[0182] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Al and Zn during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots, pure Al, and pure Zn, and preheat them in an oven at 200℃. Place the crucibles, coated with release agent, into the oven to dry.
[0183] 2) Place industrial pure magnesium ingots in a crucible and heat to 720℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add Al and Zn as pure Al and pure Zn, respectively. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and maintain the temperature at 720℃. Cast the molten Mg-Al-Zn alloy into a mold, control the solidification rate at 500 K / s, and cool to room temperature. Obtain a Mg-2Al-1Zn solid solution. Measure its thermal conductivity using ASTM-E1461 standard; it is 82 W / (m·K).
[0184] Figure 8 and Figure 9 The microstructures of Mg-2Al solid solution and Mg-2Al-1Zn solid solution are shown respectively. The comparison shows that the addition of 1 wt.% Zn to Mg-2Al solid solution did not cause Al and Zn segregation, failed to reduce the lattice distortion caused by Al atoms, and resulted in more severe electron scattering during transport, further reducing the path of freedom and thermal conductivity.
[0185] The thermal conductivity of the Mg-2Al-1Zn solid solution is lower than that of the Mg-2Al solid solution, indicating that adding the solid solution element Zn to the Mg-2Al solid solution cannot improve the thermal conductivity of the Mg-2Al solid solution.
[0186] Comparative Example 3
[0187] (1) Metal element A and metal element B and their dosages
[0188] Step 1: Select Mg as the matrix element.
[0189] Step 2: Select metal element A and metal element B:
[0190] Select the first alloying element Gd, whose solid solubility in magnesium is 4.53 at.%, greater than 1 at.%;
[0191] Select the second alloying element Li, whose solid solubility in magnesium is 17 at.%, greater than 1 at.%;
[0192] Step 3: Confirm the contents of metal element A and metal element B:
[0193] For Gd, its weight is 4 wt.% (content in the magnesium matrix);
[0194] For Li, its weight is 0.5 wt.% (content in the magnesium matrix);
[0195] According to the conversion formula between mass fraction and atomic percentage: mass percentage of Gd = atomic percentage of Gd × atomic weight of Gd / (atomic percentage of Gd × atomic weight of Gd + atomic percentage of Li × atomic weight of Li + atomic percentage of Mg × atomic weight of Mg); mass percentage of Li = atomic percentage of Li × atomic weight of Li / (atomic percentage of Gd × atomic weight of Gd + atomic percentage of Li × atomic weight of Li + atomic percentage of Mg × atomic weight of Mg). The atomic percentage of Li in the magnesium matrix is solved to be 1.79 at.%; the atomic percentage of Gd in the magnesium matrix is 0.63 at.%, and the E value of the two is 2.84, which is less than 4.
[0196] Determine the electronegativity of metal element A and metal element B:
[0197] The electronegativity of Gd is 1.2, the electronegativity of Li is 0.98, and the electronegativity of Mg is 1.31. The absolute value of the difference between the electronegativity of Gd and that of Mg is 0.11; the absolute value of the difference between the electronegativity of Li and that of Mg is 0.33; the absolute value of the difference between the electronegativity of Gd and that of Li is 0.22;
[0198] The absolute value of the electronegativity difference between Gd and Li is not greater than the absolute values of the electronegativity differences between Gd and Mg, and between Li and Mg respectively.
[0199] Determine the atomic radii of metal element A and metal element B:
[0200] The atomic radius of Gd is The atomic radius of Li is The atomic radius of Mg is Atomic radius order: Gd > Mg > Li.
[0201] (II) Preparation of Mg-4Gd solid solution
[0202] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, and preheat them in an oven at 200℃. Place the crucibles coated with release agent into the oven to dry.
[0203] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and pour into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-4Gd solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 78 W / (m·K).
[0204] (III) Preparation of Mg-4Gd-0.5Li solid solution
[0205] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd and Li during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots, Mg-Gd master alloy, and Mg-Li master alloy, and preheat them in an oven at 200℃. Place the crucibles coated with release agent into the oven to dry.
[0206] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add a Mg-Gd master alloy. After obtaining molten Mg-Gd metal, lower the temperature to 700℃ and add a Mg-Li master alloy to the Mg-Gd alloy melt. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, raise the temperature to 750℃, and pour the molten Mg-Gd-Li alloy into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain a Mg-4Gd-0.5Li solid solution. Measure its thermal conductivity using ASTM-E1461 standard; it is 70 W / (m·K).
[0207] Figure 1 and Figure 10 schematically show the microstructures of the Mg-4Gd solid solution and the Mg-4Gd-0.5Li solid solution respectively. It can be seen from the comparison that adding 0.5 wt.% Li into the Mg-4Gd solid solution does not cause segregation of Li and Gd, fails to alleviate the lattice distortion caused by Gd atoms, which leads to more severe scattering of electrons during transportation, further reduces the free path, and lowers the thermal conductivity.
[0208] The thermal conductivity of the Mg-4Gd-0.5Li solid solution < the thermal conductivity of the Mg-4Gd solid solution, which indicates that adding the solid solution element Li into the Mg-4Gd solid solution cannot improve the thermal conductivity of the Mg-4Gd solid solution.
[0209] Comparative Example 4
[0210] (1) Metal element A and metal element B and their dosages
[0211] Step 1: Select Mg as the matrix element.
[0212] Step 2: Select metal element A and metal element B:
[0213] Select the first alloying element Gd, whose solid solubility in magnesium is 4.53 at.%, greater than 1 at.%;
[0214] Select the second alloying element Y, whose solid solubility in magnesium is 3.4 at.%, greater than 1 at.%;
[0215] Step 3: Confirm the contents of metal element A and metal element B:
[0216] Gd is taken at a weight of 4 wt.% (content in the magnesium matrix);
[0217] Y is taken at a weight of 1 wt.% (content in the magnesium matrix);
[0218] According to the conversion formula between mass fraction and atomic percentage: mass percentage of Gd = atomic percentage of Gd × atomic weight of Gd / (atomic percentage of Gd × atomic weight of Gd + atomic percentage of Y × atomic weight of Y + atomic percentage of Mg × atomic weight of Mg); mass percentage of Y = atomic percentage of Y × atomic weight of Y / (atomic percentage of Gd × atomic weight of Gd + atomic percentage of Y × atomic weight of Y + atomic percentage of Mg × atomic weight of Mg). The calculated atomic percentage of Y in the magnesium matrix is 0.29 at.%; the atomic percentage of Gd in the magnesium matrix is 0.64 at.%, and the E value of the two is 0.45, which is less than 4.
[0219] Determine the electronegativity of metal element A and metal element B:
[0220] The electronegativity of Gd is 1.2, that of Y is 1.22, and that of Mg is 1.31. The absolute value of the difference between the electronegativity of Gd and Mg is 0.11; the absolute value of the difference between the electronegativity of Y and Mg is 0.09; and the absolute value of the difference between the electronegativity of Gd and Y is 0.02.
[0221] The electronegativity difference between Gd and Y is not greater than the electronegativity difference between Gd and Y and Mg, respectively;
[0222] Determine the atomic radii of metal element A and metal element B:
[0223] The atomic radius of Gd is The atomic radius of Y is The atomic radius of Mg is Atomic radius order: Y > Gd > Mg;
[0224] (II) Preparation of Mg-4Gd solid solution
[0225] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, and preheat them in an oven at 200℃. Place the crucibles coated with release agent into the oven to dry.
[0226] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and pour into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-4Gd solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 78 W / (m·K).
[0227] (III) Preparation of Mg-4Gd-1Y solid solution
[0228] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd and Y during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots, Mg-Gd master alloy, and Mg-Y master alloy, and preheat them in an oven at 200℃. Place the crucibles coated with release agent into the oven to dry.
[0229] 2) Place the industrial pure magnesium ingot into a crucible, heat it up to 760°C in a protective atmosphere filled with a mixed gas of SF6 and CO2 (volume ratio 60:1). After 80 minutes, when the pure magnesium is melted, add the Mg-Gd master alloy. After obtaining the molten Mg-Gd metal liquid, maintain the temperature at 760°C, add the Mg-Y master alloy into the Mg-Gd alloy melt, stir thoroughly for 15 minutes, stand for 20 minutes, skim off the slag, cast the molten Mg-Gd-Y alloy into a mold, control the alloy to solidify at a solidification rate of 500K / s, and cool it to room temperature. The Mg-4Gd-1Y solid solution is obtained, and its thermal conductivity is measured to be 72W / (m·K) using the ASTM-E1461 test standard.
[0230] Figure 1 and Figure 11 respectively show the schematic microstructures of the Mg-4Gd solid solution and the Mg-4Gd-1Y solid solution. It can be seen from the comparison that adding 1wt.% Y to the Mg-4Gd solid solution does not cause segregation of Y and Gd, fails to reduce the lattice distortion caused by Gd atoms, resulting in more severe scattering of electrons during transportation, a further reduced free path, and a decreased thermal conductivity.
[0231] The thermal conductivity of the Mg-4Gd-1Y solid solution is lower than that of the Mg-4Gd solid solution, indicating that adding the solute element Y to the Mg-4Gd solid solution cannot improve the thermal conductivity of the Mg-4Gd solid solution.
[0232] Comparative Example 5
[0233] (1) Metal element A, metal element B and their dosages
[0234] Step 1: Select Mg as the matrix element.
[0235] Step 2: Select metal element A and metal element B:
[0236] Select the first element Gd, whose solid solubility in magnesium is 4.53at.%, greater than 1at.%;
[0237] Select the second element Al, whose solid solubility in magnesium is 11.44at.%, greater than 1at.%.
[0238] Step 3: Confirm the contents of metal element A and metal element B:
[0239] For Gd, its weight is 3wt.% (content in the magnesium matrix);
[0240] For Al, its weight is 4wt.% (content in the magnesium matrix);
[0241] Based on the conversion formula between mass fraction and atomic percentage: Mass percentage of Gd = Atomic percentage of Gd × Atomic weight of Gd / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Al × Atomic weight of Al + Atomic percentage of Mg × Atomic weight of Mg); Mass percentage of Al = Atomic percentage of Al × Atomic weight of Al / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Al × Atomic weight of Al + Atomic percentage of Mg × Atomic weight of Mg). Solving for the atomic percentage of Al in the magnesium matrix, we find it to be 3.71 at.%, and the atomic percentage of Gd in the magnesium matrix to be 0.48 at.%. The equation E = 7.73, which is greater than 4.
[0242] Determine the electronegativity of metal element A and metal element B: Same as in Example 1;
[0243] Determine the atomic radii of metal element A and metal element B: Same as in Example 1.
[0244] (II) Preparation of Mg-3Gd solid solution
[0245] 1) Based on the alloy composition and stoichiometric ratio, and considering the loss of Gd during the smelting process, the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, were deoxideized and placed in an oven for preheating at 200℃. The crucibles, coated with release agent, were then placed in the oven for drying.
[0246] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and pour into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-3Gd solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 85 W / (m·K).
[0247] (III) Preparation of Mg-3Gd-4Al solid solution
[0248] 1) Based on the alloy composition and stoichiometric ratio, and considering the loss of Gd and Al during the smelting process, the required raw materials, including industrial pure magnesium ingots, Mg-Gd master alloy, and pure Al, were deoxideized and placed in an oven for preheating at 200℃. The crucibles, coated with release agent, were then placed in the oven for drying.
[0249] 2) Place the industrial pure magnesium ingot into a crucible, heat it up to 760°C in a protective atmosphere filled with a mixed gas of SF6 and CO2 (volume ratio 60:1), wait for 80 minutes until the pure magnesium is melted, then add the Mg-Gd master alloy. After obtaining the molten Mg-Gd metal liquid, wait until the temperature drops to 700°C, add Al to the Mg-Gd alloy melt in the form of pure Al, stir thoroughly for 15 minutes, let it stand for 20 minutes, remove the slag, heat up to 750°C, transfer the molten Mg-Gd-Al alloy into a mold, control the alloy to solidify at a solidification rate of 500K / s, and cool it to room temperature. The Mg-3Gd-4Al solid solution is obtained, and its thermal conductivity is measured to be 80W / (m·K) using the ASTM-E1461 test standard.
[0250] Figure 12 is a schematic microstructure diagram of the Mg-3Gd-4Al solid solution. By comparison Figure 3 , it can be seen that when 4wt.% Al is added to the Mg-3Gd solid solution, in addition to the segregation of part of Al and Gd, excess Al is uniformly dispersed in the magnesium matrix. Although the segregation of Al and Gd reduces the lattice distortion caused by Gd atoms, the excess Al atoms will cause additional lattice distortion, leading to the scattering of electrons during transportation, the free path is reduced instead, and thus the thermal conductivity decreases.
[0251] The thermal conductivity of the Mg-3Gd-4Al solid solution is lower than that of the Mg-3Gd solid solution, which indicates that adding an excessive amount of multi-component solid solution elements will reduce the thermal conductivity of the Mg-3Gd solid solution.
[0252] Comparative Example 6
[0253] (1) Metal element A and metal element B and their dosages
[0254] Step 1: Select Mg as the matrix element.
[0255] Step 2: Select metal element A and metal element B:
[0256] Select the first alloying element Gd, whose solid solubility in magnesium is 4.53at.%, greater than 1at.%;
[0257] Select the second alloying element Zn, whose solid solubility in magnesium is 2.4at.%, greater than 1at.%.
[0258] Step 3: Confirm the contents of metal element A and metal element B:
[0259] For Gd, its weight content is 3wt.% (content in the magnesium matrix);
[0260] For Zn, its weight content is 5wt.% (content in the magnesium matrix);
[0261] Based on the conversion formula between mass fraction and atomic percentage: Mass percentage of Gd = Atomic percentage of Gd × Atomic weight of Gd / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Zn × Atomic weight of Zn + Atomic percentage of Mg × Atomic weight of Mg); Mass percentage of Zn = Atomic percentage of Zn × Atomic weight of Zn / (Atomic percentage of Gd × Atomic weight of Gd + Atomic percentage of Zn × Atomic weight of Zn + Atomic percentage of Mg × Atomic weight of Mg). Solving for Zn in the magnesium matrix yields an atomic percentage of 1.97 at.% and Gd in the magnesium matrix, with E = 4.02, which is greater than 4.
[0262] Determine the electronegativity of metal element A and metal element B: Same as in Example 3;
[0263] Determine the atomic radii of metal element A and metal element B: Same as in Example 3.
[0264] (II) Preparation of Mg-3Gd solid solution
[0265] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots and Mg-Gd master alloy, and preheat them in an oven at 200℃. Place the crucibles coated with release agent into the oven to dry.
[0266] 2) Place industrial pure magnesium ingots in a crucible and heat to 760℃ in a protective atmosphere of a mixture of SF6 and CO2 (volume ratio 60:1). After 80 minutes, once the pure magnesium has melted, add the Mg-Gd master alloy. Stir thoroughly for 15 minutes, let stand for 20 minutes, remove slag, and pour the molten Mg-Gd alloy into a mold. Control the alloy to solidify at a solidification rate of 500 K / s and cool to room temperature. Obtain the Mg-2Gd solid solution. Measure its thermal conductivity using the ASTM-E1461 standard; it is 85 W / (m·K).
[0267] (III) Mg-3Gd-5Zn solid solution
[0268] 1) First, according to the alloy composition and stoichiometric ratio, considering the loss of Gd and Zn during the smelting process, remove the oxide layer from the required raw materials, including industrial pure magnesium ingots, Mg-Gd master alloy, and pure Zn, and preheat them in an oven at 200℃. Place the crucibles, coated with release agent, into the oven to dry.
[0269] 2) Put the industrial pure magnesium ingot into a crucible, heat it up to 760°C in a protective atmosphere filled with a mixed gas of SF6 and CO2 (volume ratio of 60:1), wait for 80 minutes until the pure magnesium is melted, then add the Mg-Gd master alloy. After obtaining the molten Mg-Gd metal liquid, wait for the temperature to drop to 700°C, add Zn to the Mg-Gd alloy melt in the form of pure Zn, stir thoroughly for 15 minutes, stand still for 20 minutes, skim off the slag, heat up to 750°C, cast the molten Mg-Gd-Zn alloy into a mold, control the alloy to solidify at a solidification rate of 500K / s, and cool it to room temperature. The Mg-2Gd-1Zn solid solution is obtained, and its thermal conductivity is measured to be 69W / (m·K) using the ASTM-E1461 test standard.
[0270] Figure 13 is a schematic diagram of the microstructure of the Mg-3Gd-5Zn solid solution, by comparison Figure 3 , it can be seen that after adding 5wt.% Zn to the Mg-3Gd solid solution, in addition to the segregation of part of Zn and Gd, there is excess Zn uniformly dispersed in the magnesium matrix. Although the segregation of Zn and Gd reduces the lattice distortion caused by Gd atoms, the excess Zn atoms will cause additional lattice distortion, leading to scattering of electrons during transportation, the free path is reduced instead, and thus the thermal conductivity decreases.
[0271] The thermal conductivity of the Mg-3Gd-5Zn solid solution is lower than that of the Mg-3Gd solid solution, which indicates that adding excessive multi-component solid solution elements will reduce the thermal conductivity of the Mg-3Gd solid solution.
[0272] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various variations or modifications within the scope of the claims, which do not affect the essential content of the present invention.
Claims
1. A design method for a high thermal conductivity multi-component magnesium alloy solid solution, characterized in that, The method includes the following steps: S1. Magnesium was chosen as the matrix element; S2. Choose metal element A, which has a certain solid solubility in the magnesium matrix; choose metal element B, which also has a certain solid solubility in the magnesium matrix. S3. Confirm the content of selected metal element A and metal element B: The ratio of the atomic percentage at.% of element B in the magnesium matrix to the atomic percentage at.% of element A in the magnesium matrix is denoted as E; if E≤4, the content of metal element A and metal element B is qualified; if E>4, the content of metal element A and metal element B is unqualified and the content needs to be re-determined. Determine the electronegativity of metal element A and metal element B; the absolute value of the electronegativity difference between metal element A and Mg atom is denoted as Y1, the absolute value of the electronegativity difference between metal element B and Mg atom is denoted as Y2, and the absolute value of the electronegativity difference between metal element B and metal element A is denoted as Y3. If Y3 is greater than both Y1 and Y2, then metal element A and metal element B are qualified; otherwise, metal element A and metal element B are unqualified. Determine the atomic radii of metal element A and metal element B; determine whether the atomic radii of metal element A and metal element B are both greater than or both less than the atomic radius of Mg; if not, then metal element A and metal element B are qualified; if so, then metal element A and metal element B are unqualified.
2. The design method according to claim 1, characterized in that, In S1, the solid solubility limit of element A in the magnesium matrix is ≥1 at.%; the solid solubility limit of element B in the magnesium matrix is ≥1 at.%.
3. A method for preparing a magnesium alloy solid solution, characterized in that, Includes the following steps: 1) Using the design method for high thermal conductivity multi-component magnesium alloy solid solution as described in claim 1 or 2, confirm metal element A and its content; and metal element B and its content; 2) Weigh the raw materials according to the stoichiometric ratio; add element A to the magnesium matrix, melt, and obtain Mg-A alloy melt; 3) Add element B to the Mg-A alloy melt, melt it, and obtain the Mg-AB alloy melt; 4) Solidify the Mg-AB alloy melt at a certain solidification rate and cool it to ambient temperature to obtain the magnesium alloy solid solution.
4. The preparation method according to claim 3, characterized in that, In step 2), the melting conditions are: temperature 700-800℃, time 60-100min.
5. The preparation method according to claim 3, characterized in that, In step 2), melting is carried out under a protective atmosphere, which includes SF6 and CO2.
6. The preparation method according to claim 3, characterized in that, In step 3), the melting conditions are: temperature 700-800℃, time 10-30min.
7. The preparation method according to claim 3, characterized in that, In step 4), the solidification rate is 400-800 K / s.
8. The preparation method according to claim 3, characterized in that, Element A is selected from Gd or Al; element B is selected from Al, Zn, or Gd; elements A and B are not the same.
9. A magnesium alloy solid solution prepared by the preparation method according to any one of claims 3-8.
10. The magnesium alloy solid solution according to claim 9, characterized in that, The magnesium alloy solid solution includes one of Mg-3Gd-1Al, Mg-4Gd-2Al, and Mg-2Gd-1Zn solid solutions.
Citation Information
Patent Citations
As-cast high-strength-and-toughness ma.gnesium-lithium alloy and preparation method thereof
CN103290286A
Improved magnesium alloy and process for making the same
CN112334587A